Charismatic Leadership: A Traditional Review - Gursoy, Elif; Ünülü, Meryem (Şefika Şule ERÇETİN, 2025)
Leadership as a concept has captured the interest of countless people from ancient times to the present, and is becoming increasingly popular today. Some of the exemplary and influential military, political, religious and social leaders in historical texts have been described as charismatic leaders. Charismatic leaders are defined as leaders who are characterized by an ability of divine inspiration, those who possess this ability or have this impact. There are a number of leadership behaviors that distinguish charismatic leaders from non-charismatic leaders. The fundamental behaviors of charismatic leadership may differ between theories and sometimes between older and newer versions of the same theory. As we look at examples of charismatic leaders, we see both positive and negative aspects of charismatic leadership. Charismatic leaders, to whom followers unconditionally submit and unquestioningly trust, may choose to glorify themselves by ignoring common values and mission if they cannot be subjected to scrutiny. In such cases, we are faced with negative and toxic charismatic leaders. Followers' approval of the toxic leader's behavior, for whatever reason, ensures the continuation of negative attitudes and behaviors. The emergence of toxic leaders can be prevented by finding and preventing the reasons that lead the leader to become a toxic leader. In studies conducted on leadership and leadership styles in the health sector, it is seen that the effects of charismatic leadership are indirectly addressed and that charismatic leadership makes significant contributions to areas such as patient care quality and team performance.

Liderlik, konusu eski dönemlerden bugüne kadar birçok insanın dikkatini çekmiş ve günümüzde popülerliği giderek artan bir kavram haline gelmiştir. Tarih metinlerinde askeri, siyasi, dini ve toplumsal örnek ve etkili liderlerden bazıları karizmatik liderler olarak tanımlanmıştır. İlahi ilham yeteneği vurgusu ile anılan ve bu yeteneği taşıyan ya da bu etkiyi gösteren liderler karizmatik lider olarak tanımlanmaktadır. Karizmatik liderliği karizmatik olmayan liderlikten ayıran bir dizi lider davranışı vardır. Karizmatik liderliğin temel davranışları teoriden teoriye ve bazen de aynı teorinin eski versiyonlarından yeni versiyonlarına farklılık gösterebilmektedir. Lider örneklerine baktığımızda olumlu ve olumsuz karizmatik lider örnekleri ile karşılaşmaktayız. Takipçilerinin koşulsuz olarak boyun eğdiği, sorgulamadan güvendiği karizmatik liderler denetlenemez ise ortak değerler ve misyona önem vermeyerek kendini yüceltmeyi seçebilmektedirler. Bu durumda olumsuz ve toksik karizmatik liderler karşımıza çıkmaktadır. Toksik liderler, bulundukları kurum ya da toplumun performansını olumsuz etkileyebilmektedir. Takipçilerin hangi nedenle olursa olsun toksik liderin davranışlarını onaylaması, olumsuz tutum ve davranışların devamlılığını sağlar. Lideri, toksik lider olmaya yönlendiren sebeplerin bulunup, önlenmesi ile birlikte toksik liderlerin ortaya çıkışı engellenebilir. Sağlık sektöründe liderlik ve liderlik tarzları üzerine yapılan araştırmalarda, karizmatik liderliğin etkilerinin dolaylı olarak ele alındığı, karizmatik liderliğin hasta bakım kalitesi ve ekip performansı gibi alanlarda önemli katkılar sağladığı görülmektedir.
Karizmatik Liderlik: Geleneksel Derleme
Keywords: Leadership; Liderlik